2018
DOI: 10.3892/ol.2018.9869
|View full text |Cite
|
Sign up to set email alerts
|

Metformin attenuates hypoxia‑induced resistance to cisplatin in the HepG2 cell line

Abstract: Hepatoblastoma is the most commonly occurring liver tumor in children. Preoperative chemotherapy and surgery have improved treatment outcomes; however, further improvements are required in the treatment of advanced cases. Recently, the efficacy of transarterial chemoembolization (TACE) has garnered attention. TACE increases the local concentration of drugs by transcatheterically administering antitumor agents, and induces necrosis in the tumor by embolizing the feeding artery. However, studies have revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…The restoration of YAP partially undermined the inhibitive effect of MEL on HCC cells, suggesting MEL involved in Hippo signaling. Accumulating studies also implied that MEL enhances cisplatin anti-cancer effect in many cancer cells by stimulating mitochondrial ROS generation, 41 this aspect requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The restoration of YAP partially undermined the inhibitive effect of MEL on HCC cells, suggesting MEL involved in Hippo signaling. Accumulating studies also implied that MEL enhances cisplatin anti-cancer effect in many cancer cells by stimulating mitochondrial ROS generation, 41 this aspect requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…More studies are needed to confirm if, in the GC context, the association of metformin with conventional chemotherapies represents an interesting therapeutic perspective, as it is the case in hepatoblastoma for example, where metformin attenuated hypoxia-induced resistance to cisplatin in the human liver cancer cell line HepG2 [64]. This study clearly demonstrated that addition of metformin is better than conventional chemotherapy alone.…”
Section: Can Metformin Be An Interesting Candidate To Combine With Comentioning
confidence: 62%
“…Metformin successfully restored chemosensitivity to cisplatin in hepatoblastoma cells under hypoxia. 86 Conversely, the inhibitory effects of metformin on tumour growth were reduced by hypoxia in childhood sarcoma xenografts. 87 The disparity in results may be due to the inherent differences between hepatomas and sarcomas and/or the variabilities in experimental details, including drug concentrations and methods used to induce hypoxia.…”
Section: Hypoxia-targeted Treatment Strategy 1: Increasing Oxygen Avamentioning
confidence: 99%